The completeness of national hip and knee replacement registers. - FRENCH, Jonathan M. R.; DEERE, Kevin; WHITEHOUSE, Michael R.; PEGG, Derek J.; CIMINELLO, Enrico; VALENTINI, Riccardo; TORRE, Marina; MÄKELÄ, Keijo; LÜBBEKE, Anne; BOHM, Eric R.; FENSTAD, Anne Marie; FURNES, Ove; et al. (Acta Orthopaedica, 2024)
Background and purpose -- National joint replacement registries were developed for prospective monitoring of outcomes and post-market surveillance of implants. Increasingly registry data informs practice. However, analysis of a registry can only be as good as the data it captures on the population of interest. We aimed to analyze completeness of reporting of hip and knee replacement procedures for all national registries worldwide. Methods -- We analyzed annual reports and data provided following written requests to all active national hip and knee replacement registries. Coverage was defined as the proportion of hospitals in the country that participate in the registry. Procedure completeness was defined as the proportion of procedures successfully captured by the registry. Results -- 14 national registries were included, spanning years 2004 to 2022. Coverage was complete in 10. Median procedure completeness for primary hip and knee replacement across all years was 96.5% (interquartile range [IQR] 94.0-97.7%). Median procedure completeness for revisions was 88.5% (IQR 81.0-92.5%). The terminology used and method of calculation of completeness estimates in the registries were variable. Conclusion -- National hip and knee replacement registry data generally reflects excellent coverage (full in 10 of 14 registries) and completeness (primary procedures 96.5% and revisions 88.5%) over the last 2 decades.